Analysis of the physical fitness and determinants of performance of beach handball athletes - Francine De Oliveira; Victor Gonçalves Corrêa Neto; Gilson Ramos de Oliveira Filho; Marcel Lima Lessa de Souza; Jaime Souza Torres; Wellington Esteves; Rudney Uezu; Igor Ramathur Telles de Jesus; Estêvão Rios Monteiro (Elsevier, 2024)
Introduction: Beach handball, an emerging team sport derived from indoor handball, is characterized by high-intensity efforts. This study aimed to analyze the physical fitness profiles of elite beach handball players of both sexes and identify the characteristics that determine anaerobic power performance among these athletes. Material and methods: A cross-sectional study was conducted with 25 elite beach handball players. Anaerobic power, sprint performance, and change-of-direction ability were assessed. Results: There were no significant differences between men and women in anaerobic power and change-of-direction ability. Men showed better performance in the 15-meter sprint test (p = 004). A moderately strong positive correlation was found between anaerobic power and age. BMI did not significantly correlate with power performance. Conclusions: Age is an important determinant of anaerobic power, whereas body mass index does not play a significant role, especially among males.